Repeat examinations in conventional radiology analysis - Freitas, Artur (2022)
Introduction: CR is the first-line method for diagnosing various pathologies and evaluating anatomy. The repetition of these exams is related to the non-fulfillment of good performance criteria that result in an absence/insufficiency of diagnostic value. The decrease in the repetition rate represents an important factor in the area of radiology and community health, contributing to the decrease in the dose received by patients and health professionals. The main objective of this study was to determine which conventional radiology exams are more likely to be repeated by radiology technicians, and their respective causes. Methods: An analytical, observational, and cross-sectional study was carried out. Data were collected by applying an online questionnaire survey to study participants. The study population consisted of Portuguese radiology technicians, graduated in radiology or medical imaging and radiotherapy, working in Portugal or abroad. For the study of associations between variables, the statistical tests of Pearson's correlation and chi-square of independence were used. Results: The sample consisted of 228 participants, of which 176 (77.2%) were female, with an average age of 33.93 (±10.37) years and average length of professional experience of 10.58 (±10.34) years. The knee examination (61%) was considered by the participants as the most likely to be repeated, followed by the chest (29.4%) and shoulder (24.6%). The participants mentioned incorrect positioning as the most common technical error, with the patient's non-cooperation being the main predictor of technical error. A weak negative correlation was observed between the length of experience of professionals and the frequency with which they repeat radiological exams. Conclusion: The exams performed on the knee, shoulder and chest are those with the highest repetition rate, and the most common error the patient's incorrect positioning. The factor that most contributes for the technician to make mistakes is the patient's non-cooperation. Participants emphasize the need to develop continuing training programs and the introduction of short breaks during shifts.